Sanksi Pidana Untuk Perlindungan Anak Sebagai Korban Eksploitasi Berdasarkan Undang-Undang Nomor 35 Tahun 2014 - Miasiratni (Universitas Sumatera Barat, 2023)
Children are a blessing in the family. Children should be protected and have their rights respected. It is natural for the state to guarantee and protect children's rights. Both civil, social, political, cultural and economic. In reality, families and even the state have not been able to provide adequate welfare for children. One of the problems that still occurs is the exploitation of children, which not only violates children's rights, but also has a negative impact on children both physically and psychologically. Child exploitation shows arbitrary treatment of children carried out by families and society. Forcing children to do something for economic, social or political interests without paying attention to the child's right to receive protection in accordance with their physical, psychological development and social status. This method uses normative legal research methods, namely examining laws that are conceptualized as applicable norms or rules, including child protection laws and related regulations. The results of this research show that the people most responsible for child protection are the parents. Therefore, it can be said to intentionally exploit children by seeking commercial profits from their work and acts of violence against children. The provisions that can ensnare those who carry out exploitation are Law Number 35 of 2014 concerning Child Protection. Second research results. The threat of sanctions against perpetrators of violence, both in child protection laws and the Criminal Code, are some that are heavier and some that are lighter. But in Law Number 35 of 2014, apart from physical threats there are also threats of fines and threats of minimum sanctions, in the Criminal Code there are only physical threats, there are no minimum threats.